Evaluating the Impact of Computer-Based Testing with Tryout Methodology on Students Numeracy Literacy Development - Saluky Saluky; Hadi Kusmanto; Dzakiyyah Rosyidah S (EduMa: Mathematics education learning and teaching, 2025)
This study investigates the impact of Computer-Based Testing (CBT) with a tryout methodology on students’ numeracy literacy development. The research aims to determine whether repeated exposure to digital tryout-style assessments can significantly improve students’ understanding and application of numeracy concepts. A quasi-experimental design was employed, involving 240 students from several grade levels, who were divided into experimental and control groups. The experimental group engaged in weekly CBT tryouts focused on numeracy problems, while the control group underwent traditional paper-based assessments over a six-week period. Pre- and post-intervention tests were conducted using standardized numeracy instruments to evaluate skills such as number sense, mathematical reasoning, problem-solving, and interpretation of quantitative information. The results showed a statistically significant improvement in the experimental group’s post-test scores compared to the control group (t(238) = 8.91, p < 0.001). The calculated effect size (Cohen’s d = 1.47) indicated a strong impact of the CBT tryout method on numeracy literacy development. Qualitative feedback from students in the experimental group also revealed higher engagement, reduced test anxiety, and increased familiarity with digital testing environments. These findings suggest that integrating CBT with a tryout methodology can serve as an effective instructional and assessment strategy to support numeracy development, particularly in preparing students for computer-based national and standardized tests.